If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(4y + -6) + 6y = 4(y + 4) Reorder the terms: -3(-6 + 4y) + 6y = 4(y + 4) (-6 * -3 + 4y * -3) + 6y = 4(y + 4) (18 + -12y) + 6y = 4(y + 4) Combine like terms: -12y + 6y = -6y 18 + -6y = 4(y + 4) Reorder the terms: 18 + -6y = 4(4 + y) 18 + -6y = (4 * 4 + y * 4) 18 + -6y = (16 + 4y) Solving 18 + -6y = 16 + 4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4y' to each side of the equation. 18 + -6y + -4y = 16 + 4y + -4y Combine like terms: -6y + -4y = -10y 18 + -10y = 16 + 4y + -4y Combine like terms: 4y + -4y = 0 18 + -10y = 16 + 0 18 + -10y = 16 Add '-18' to each side of the equation. 18 + -18 + -10y = 16 + -18 Combine like terms: 18 + -18 = 0 0 + -10y = 16 + -18 -10y = 16 + -18 Combine like terms: 16 + -18 = -2 -10y = -2 Divide each side by '-10'. y = 0.2 Simplifying y = 0.2
| 15b^2-24b-63=0 | | .35x-x^2=670 | | 6x-10+2x-4=90 | | 21x^2-46xy+13y^2=0 | | 7(y-1)=5y+5-2(-8y-2) | | 3+21nx=4 | | =32a^2-50 | | (5x+7)(5x+7)-(5x-7)(5x-7)=140x | | 32a^2-50= | | X^2-xy+y^2=63 | | (5x+7)2-(5x+7)2=140x | | y^2(x+1)+9y(x+1)+20(x+1)=0 | | 5v-6+2(2v+1)=-5(v+2) | | 32x+2x^2+126=0 | | 25a^2+40ab+16b^2= | | n^2-12n-42=3 | | -5(-3v+2)-v=6(v-2)-2 | | 21+5y-6=17y-9 | | 57(.1)=2x+57x | | 6(y+5)=-5(2y-8)+8y | | x^3y^2+x^2y-56x=0 | | 6+x=-6-x | | 21+5y-6=17y-9-4y | | -2+15=3b-7-2b | | .28x=(.5-x) | | (x*x)+9=-[(x*x)+9] | | x^7-13x^6-48x^5=0 | | 7.7=3.2+s | | 5x^5+65x^4+180x^3=0 | | -1.4=-b | | n^2-4n+35=0 | | 3-/8=-2 |